Screening and Functional Analysis of TEK Mutations in Chinese Children With Primary Congenital Glaucoma - Qiao, Yunsheng; Chen, Yuhong; Tan, Chen; Sun, Xinghuai; Chen, Xueli; Chen, Junyi (Frontiers in Genetics, 2021)
Purposes: Recent studies have suggested that loss-of-function mutations of the tunica intima endothelial receptor tyrosine kinase (TEK) are responsible for approximately 5% of primary congenital glaucoma (PCG) cases in diverse populations. However, the causative role of TEK mutations has not been studied in Chinese PCG patients. Here, we report the mutation spectrum of TEK after screening a large cohort of PCG patients of Chinese Han origin and analyze the identified variants in functional assays. Methods: TEK-targeted next generation sequencing (NGS) was performed in 200 PCG patients. Candidate variants were prioritized by mutation type and allele frequency in public datasets. Plasmids containing wild type as well as identified variants of TEK were constructed and used to assess protein expression, solubility, receptor auto-phosphorylation, and response to ligand stimulation in cell-based assays. Results: 10 missense and 1 nonsense heterozygous variants were detected by NGS in 11 families. The clinical features of TEK variants carriers were comparable to that of TEK-mutated patients identified in other populations and CYP1B1-mutated individuals from in-house database. Functional analysis confirmed 4 variants involving evolutionarily conserved residues to be loss-of-function, while one variant (p.R1003H) located in tyrosine kinase domain seemed to be an activating mutation. However, our results did not support the pathogenicity of the other 5 variants (p.H52R, p.M131I, p.M228V, p.H494Y, p.L888P). Conclusion: We provide evidence for TEK variants to be causative in Chinese PCG patients for the first time. Attention needs to be paid to TEK mutations in future genetic testing.